Being bullied and using drugs are associate with eating disorder symptoms in Brazilian students. Issue 3 (17th December 2020) - Galvão, Patricia Paiva de O.; Valente, Juliana Y.; Almeida, Mireille Coêlho; Gubert, Fabiane A.; Rebouças, Lidiane; Mari, Jair; Caetano, Sheila C.; Sanchez, Zila M.
Abstract: Objective: This study's main purpose is to evaluate factors associated with eating disorder (ED) symptoms among Brazilian adolescents. Method: The sample consisted of 5, 213 students, mean age 13.24 ( SD ±0.01), in the eighth grade of 93 public schools from three Brazilian cities. Data were collected through an anonymous self‐report questionnaire, assessing: sociodemographics, use of alcohol, tobacco, illicit drugs, binge drinking, bullying, and ED symptoms. We used confirmatory factor analysis and multivariate linear regression. Results: We found that high levels of bullying victimization, binge drinking and the use of unprescribed weight‐loss substances were associated with higher levels of ED symptoms to both genders. However, only among girls, the higher age ( β = .10; 95% CI = 0.02; 0.17) and the use of illicit drugs ( β = .21; 95% CI = 0.094; 0.34) were associated with increase in the ED symptoms. Discussion: We demonstrate a significant association of ED symptoms with drug use and bullying, highlighting the importance of addressing these factors in the development of ED prevention strategies.